Some Fixed Points Results of Quadratic Functions in Split Quaternions. (19th September 2016) - Kwun, Young Chel; Munir, Mobeen; Nazeer, Waqas; Kang, Shin Min
Abstract : We attempt to find fixed points of a general quadratic polynomial in the algebra of split quaternion. In some cases, we characterize fixed points in terms of the coefficients of these polynomials and also give the cardinality of these points. As a consequence, we give some simple examples to strengthen the infinitude of these points in these cases. We also find the roots of quadratic polynomials as simple consequences.